Macedonian Orthodox Church-Archbishopric of Ohrid and Its Arduous Road to Autocephaly - Gjorgjevski, Gjoko (Occasional papers on religion in Eastern Europe, 2022)
The aim of this paper is to examine the recent developments related to the Macedonian Orthodox Church-Archbishopric of Ohrid, the acceptance of the canonical status by the Ecumenical Patriarchate, and the conferring of status to autocephaly by the Serbian Orthodox Church in 2022. From the ecclesiological and the liturgical aspect, the MOC-OA is no longer in isolation and is part of the family of Orthodox churches through the restoration of Eucharistic communion. The final step, the granting of a Tomos by the Ecumenical Patriarchate is expected, which would make the MOC-OA the first by all recognized and accepted autocephalous church in the 21st century.